2017
DOI: 10.1002/ags3.12031
|View full text |Cite
|
Sign up to set email alerts
|

Are treatment outcomes in gastric cancer associated with either hospital volume or surgeon volume?

Abstract: Surgical resection is the only curative treatment for gastric cancer. Postoperative outcomes may be affected by the average or total number of surgeries carried out at an institution (hospital volume) or by a surgeon (surgeon volume). Among seven large‐scale studies that each enrolled over 10 000 patients who underwent gastrectomy, six showed that higher hospital volume contributed to a lower mortality rate after gastrectomy. Surgeon volume was also reported by three of four studies that each included over 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Failure to rescue rates were 28.1% in very low-volume hospitals versus 22.7% in very high-volume hospitals [8]. According to most definitions, institutions with an average of about 50 gastroesophageal resections for malignant indications per year are regarded as high-volume centers [10]. The reported mortality rates of our patients operated on between 1972 and 1992 were consistent with the findings of a recent retrospective cohort study based on American College of Surgeons National Surgery Quality Improvement Program (ACS NSQIP) data: 30-day mortality was 5.2% [11].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to rescue rates were 28.1% in very low-volume hospitals versus 22.7% in very high-volume hospitals [8]. According to most definitions, institutions with an average of about 50 gastroesophageal resections for malignant indications per year are regarded as high-volume centers [10]. The reported mortality rates of our patients operated on between 1972 and 1992 were consistent with the findings of a recent retrospective cohort study based on American College of Surgeons National Surgery Quality Improvement Program (ACS NSQIP) data: 30-day mortality was 5.2% [11].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, surgeon case-load was associated with postoperative mortality after radical gastrectomies for GC in few studies, as two reviews have shown (37,38). Two systematic reviews published in 2012 and 2017 did not identify any correlation between hospital volume of gastrectomies and postoperative complications in the most substantial part of reported studies (37,38). However, a higher hospital volume was associated with lower mortality rates (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews published in 2012 and 2017 did not identify any correlation between hospital volume of gastrectomies and postoperative complications in the most substantial part of reported studies (37,38). However, a higher hospital volume was associated with lower mortality rates (37,38). The assessment of the impact of hospital volume on the long-term survival of patients with radical gastrectomies for GC reached conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, different gastric cancer treatments have been developed in Japan than in Western countries. Japanese surgeons have been influential in the development of gastric cancer surgery worldwide (3) , (4) , introducing techniques such as gastrectomy with extended lymphadenectomy. In the West, major treatment strategies include more limited lymph node dissection and chemotherapy or chemoradiotherapy (5) , (6) .…”
Section: Introductionmentioning
confidence: 99%